Art historiography and iconologies between west and east - Bałus, Wojciech 1961-; Kunińska, Magdalena (Routledge, Taylor & Francis Group, 2024)
"This volume explores a basic question in the historiography of art: the extent to which iconology was a homogenous research method in its own immutable right. By contributing to the rejection of the universalizing narrative, these case studies argue that there were many strands of iconology."
"This volume is a result of the work of a number of people and institutions. An important role in its genesis was played by the academic conference 'Iconologies. Global Unity or/and Local Diversities in Art History', which took place in Krakow (23-25 May 2019) and was organised collaboratively by the Institute of Art History of the Jagiellonian University and the National Museum in Krakow. [...]" -- Acknowledgements
Keywords: Geschichte 1900-2000; Ikonologie; Kunstgeschichtsschreibung; Osteuropa; Westeuropa; Iconology / Europe / History; Iconology / Soviet Union; Konferenzschrift -- 2019 -- Krakau